AL-SUYŪṬĪ WA ITTIJᾹHᾹTUH ILᾹ AL-TAFSĪR AL-‘ILMĪ DIRᾹSAH ‘ALᾹ TAFSĪR ᾹYᾹT AL-WABᾹ - Zaeni, Ahmad; Muiz, Abdul; Hajar, Siti (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
This article discusses the tendency of TafsÄ«r 'IlmÄ« in Imam Suyuti's interpretation of the plague verses. Interestingly, as a classical commentator, he interprets the plague verses in his commentary books using the traditions of the Prophet (naqli), but he explains about the plague in addition to his commentary books by referring to the interpretation of the plague verses which are supported by scientific data. To analyze the tendency of this interpretation (ittijÄh al-tafsÄ«r), the researcher uses the theory of scientific interpretation. This research is qualitative in nature and uses content analysis methods, especially the istiqra (inductive) method. The istiqra method is used to analyze his interpretation of the plague verses that are spread in his commentaries and his books on epidemics and medicine. The purpose of this study is to reveal the indications of the trend of scientific interpretation explored by Imam SuyÅ«t}Ä« in his books on epidemics and medicine by referring to his interpretations in his commentary books, so this research is urgent to confirm the historical roots and dynamics of TafsÄ«r 'IlmÄ«, whose epistemological tendency has emerged in the era of classical scholars. The results of this study are, first, in general, the method of interpretation of Imam SuyÅ«t}Ä« is bi al-ma'á¹£Å«r. Second, Imam SuyÅ«tÄ«'s interpretation of the plague verses in á¹¬Ä'Å«n and medical themed books tends to 'Ilmi' Tafsir in terms of a more scientific explanation of the narrations that are in accordance with science, medical and socio-historical. Third, the scientific tendency in Imam SuyÅ«t}Ä«'s interpretation is in historical and medical.